Analytical expressions relating free-field and foundation ground motions in buildings with basement, considering soil-structure interaction. (1st August 2020) - Sotiriadis, Dimitris; Klimis, Nikolaos; Margaris, Basil; Sextos, Anastasios
Highlights: Kinematic SSI through ground motion recordings and substructure analysis. High frequency filtering of free-field motion due to the presence of building. Foundation to free-field motion intensity measures ratio vs frequency content. Good matching of substructure analysis with recordings data. Potential correction of within-building records to be used for GMPE development. Abstract: The present study investigates the effect of soil-structure interaction (SSI) on foundation motion recorded at accelerometric stations at the lowest storey of buildings. Towards this, four sites of instrumented buildings, having foundation and free-field ground motion recordings available, are studied in the frequency domain. The significance of such instrumentation is highlighted, especially in terms of assessing the way foundation tends to filter high frequency components of free-field motions. The well-known kinematic and inertial interaction decoupling is implemented for the sites studied and is assessed on the basis of its capability to reproduce the empirical findings and measurements. Parametric analyses are performed for each site in order to develop analytical expressions relating intensity and frequency content measures between the two motions. The expressions derived are verified through comparison with recorded data. The analysis procedure is then extrapolated to sites with various soil conditions as defined by a generic ground classification as per Eurocode 8. The produced analytical expressions can be utilized, under the conditions studied herein, for correcting motions recorded at the basement level of buildings, in order to estimate the "original" free-field ground motions. The latter being "building-free", are most appropriate for the development of new generation GMPEs that are not biased by the influence of foundation presence and structural oscillation during ground motion recordings.